Analisis Faktor Penyebab Rendahnya Cakupan Persalinan di Fasilitas Kesehatan di Wilayah Kerja Puskemas Rasie - Abdullah, Vera Iriani (Poltekkes Kemenkes Jambi, 2024)
Background: The most ideal place for giving birth is a health facility, this is in accordance with recommendations from the government to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). West Papua Province is among the 19 provinces that have not met the target of giving birth in a health facility. Method: This type of research is quantitative with a sectional analytical design. The population of this study was all mothers who had given birth in the working area of ​​the Rasie Community Health Center, Teluk Wondama Regency during the period January 2022–May 2023, totaling 86 people. The research sample was 79 mothers who had given birth and did not use health facilities. The sampling technique in this research used total sampling technique. This research to be carried out in the work area of ​​the Rasie Community Health Center, Rasie District, Teluk Wondama Regency, which will be carried out in October 2023. The instrument used is a questionnaire sheet. The data analysis used in this research is the Chi-Square test. Results: The results of the Chi Square test analysis show that the distance, culture and knowledge factors have a p-value smaller or <0.05, thus the conclusion that can be drawn is that delivery coverage is influenced by distance, culture and knowledge factors. Conclusion: Distance, culture and knowledge factors are significantly related to low delivery coverage in health facilities